Spread of invasive algae unchecked by delayed reporting across South America - Rafael L. Macêdo; Fiona S. Rickowski; Jonathan M. Jeschke; Odete Rocha (Biological Invasions, 2026)
Contextualizing the lag between detection and publication of invasive species records is critical for management and communication. Using a literature review of records spanning 1963–2023 and complementary snapshot monitoring data (2012–2016), we quantify the lag time of reporting new records by researchers and illustrate the importance of timely and more reliable tracking of Ceratium spread, a genus of bloom-forming dinoflagellates with phytosanitary and ecological impacts. Our literature review indicates that records of C. furcoides and C. hirundinella (in South America) show considerable publication delays ( C. furcoides 4.3 ± 2.6 years and C. hirundinella 4.9 ± 3.9 years), limiting early control and informed water management decisions. Our mixed-effects model revealed that publication delays have significantly decreased over time, but remain longer in Brazilian records and in reservoir and river environments. From monitoring data, C. furcoides was found at 72 sites, 53 of which remain unpublished to date, spanning urban, peri-urban, and rural water bodies in São Paulo, South America’s most populous state. The species was absent from 225 sites, often associated with slightly higher water quality and preserved vegetation. More transparent and timely reporting, including absence data, is essential to enable risk modeling and preventive planning in a changing world. Once published, such data can offer valuable insights into species distributions, enabling reconstruction of invasion routes, estimation of spread rates, and identification of potential lag phases.